Next-generation synthetic biology approaches for the accelerated discovery of microbial natural products - Lei Li (Engineering Microbiology, 2023)
Microbial natural products (NPs) and their derivates have been widely used in health care and agriculture during the past few decades. Although large-scale bacterial or fungal (meta)genomic mining has revealed the tremendous biosynthetic potentials to produce novel small molecules, there remains a lack of universal approaches to link NP biosynthetic gene clusters (BGCs) to their associated products at a large scale and speed. In the last ten years, a series of emerging technologies have been established alongside the developments in synthetic biology to engineer cryptic metabolite BGCs and edit host genomes. Diverse computational tools, such as antiSMASH and PRISM, have also been simultaneously developed to rapidly identify BGCs and predict the chemical structures of their products. This review discusses the recent developments and trends pertaining to the accelerated discovery of microbial NPs driven by a wide variety of next-generation synthetic biology approaches, with an emphasis on the in situ activation of silent BGCs at scale, the direct cloning or refactoring of BGCs of interest for heterologous expression, and the synthetic-bioinformatic natural products (syn-BNP) approach for the guided rapid access of bioactive non-ribosomal peptides.